High incidence of type II autoantibodies in pernicious anaemia. Issue 1 (January 1993) - Waters, H M; Dawson, D W; Howarth, J E; Geary, C G
Abstract : AIMS: To investigate the incidence of type II autoantibodies to intrinsic factor in pernicious anaemia. METHODS: Three hundred and forty four serum samples submitted for intrinsic factor antibody (IFAB) analysis on clinical or laboratory grounds were tested by an established radioassay and a new enzyme linked immunosorbent assay (ELISA) method for type I and total IFAB, respectively. Sixty of these were found to be positive by ELISA; this method was used to test further, 40 samples of adequate volume for types I and II antibodies. RESULTS: Type II antibodies were detected in 39 of the 40 sera tested. A comparative analysis indicated that seven samples contained pure type II antibody, being positive for total and type II by ELISA, but negative for type I by both the ELISA and radioassay technique. CONCLUSIONS: The occurrence of type II antibody, both alone and in combination with type I, seems to be more common than has previously been recognised, and emphasises the advantage of using a technique which will detect both types of antibody.